Utilization of statistical process control in an experimental activity at the Federal Institute of Ceará (Research, Society and Development, 2019)
As technology advances, chemical analysis laboratories use statistical techniques to demonstrate the accuracy and precision of analytical methods. To make comparisons between the data obtained from an analysis, Statistical Process Control (CEP) can be used, which is a technique widely used in industry to understand and improve process performance through statistical data processing. Control charts are CEP graphic methods that enable continuous control of analytical processes and allow evaluations and possible optimization of assays. The objective of this study is to use the Statistical Process Control (CEP), the control chart, to evaluate the statistical stability of the spectrophotometer used in the application of the Nimodipino analytical methodology validation technique, using data from the absorbance study of this drug, being the tests performed by students contributing to a learning of work activities. With this study it can be verified that the use of the control chart generates an adequate monitoring to evaluate data fluctuations and to carry out studies of the same, being able to be taught to the students and applied in practical classes accompaniments. It can also be demonstrated that the Minitab 17 program assists quickly in the construction of control charts, obtaining real-time analysis results. This program can be used in other laboratories of the Federal Institute of Ceará for statistical control of analyzes with support for student learning.